2012
DOI: 10.1007/978-1-4614-4118-2_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MASP-1/3 in Complement Activation

Abstract: The complement system, which consists of more than 30 plasma and cell surface proteins, is activated by three pathways: the classical, lectin, and alternative pathways, leading to the generation of opsonins and pathogen destruction. In the lectin pathway, mannose-binding lectin (MBL) and ficolins act as pattern recognition molecules for pathogens, resulting in the activation of MBL-associated serine proteases (MASPs: MASP-1, MASP-2, and MASP-3). Among these proteases, MASP-2 is a key enzyme that cleaves C4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Once activated, MBL or ficolin binds mannose-binding lectin serine peptidases (MASPs), a set of three proteins that cleave C2 and C4 (Sekine et al, 2013). Upon cleavage of C2 and C4, the lectin pathway merges with the classical pathway (Wallis et al, 2010).…”
Section: The Complement System: Overviewmentioning
confidence: 99%
“…Once activated, MBL or ficolin binds mannose-binding lectin serine peptidases (MASPs), a set of three proteins that cleave C2 and C4 (Sekine et al, 2013). Upon cleavage of C2 and C4, the lectin pathway merges with the classical pathway (Wallis et al, 2010).…”
Section: The Complement System: Overviewmentioning
confidence: 99%
“…Other physiological molecular partners of MASP-3 in this context remain to be identified. It has also been proposed that murine MASP-1 and/or MASP-3 (since they are encoded by the same MASP1 gene) could be involved in activation of the alternative complement pathway through cleavage of pro-factor D [19], but this remains a controversial issue since a recent study showed that in humans both MASPs are dispensable for activation of the alternative pathway [10]. In addition, activation of MASP-3 by MASP-1 has been recently reported [10], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, due to its cross-talk with the other complement pathways CCP and CAP, components of the CLP might serve as a therapeutic target. The key proteins of the CLP are the mannose-binding lectin-associated serine proteases (MASPs, which are similar to C1r and C1s), which act by cleaving C4 [157]. MASP-2 is the molecule involved in the activation of the CCP, which thus play a major role in the well-established typical CLP [157].…”
Section: Selective Inhibitors Of the Lectin/mannose Pathwaymentioning
confidence: 99%
“…The key proteins of the CLP are the mannose-binding lectin-associated serine proteases (MASPs, which are similar to C1r and C1s), which act by cleaving C4 [157]. MASP-2 is the molecule involved in the activation of the CCP, which thus play a major role in the well-established typical CLP [157]. In contrast, it has been reported that MASP-3 may be crucial for the proper functioning of the CAP by activating CFD [158], even if this role may be somehow redundant [159].…”
Section: Selective Inhibitors Of the Lectin/mannose Pathwaymentioning
confidence: 99%